Some aspects of the micro-arthropod fauna in the soils of pineapple fields in the Bathurst division, Eastern Cape Province - Graham, P (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1956)
Although a considerable amount of work has been done on the fauna of the soil of temperate forests and pastures, very little is known about that of tropical and sub-tropical soils. Most of the work on tropical soils concerns the fauna of tropical forests ... . The present investigation represents an attempt to discover the effect of an imported perennial tropical and sub-tropical plant, the Pineapple, on the soil fauna of a semi-arid region (rainfall 15-25 inches). Intro., p. 1-2
Keywords: Pineapple; Soils -- South Africa -- Eastern Cape; Soil surveys -- South Africa -- Eastern Cape; Soil science; Arthropoda -- South Africa; Arthropod pests -- South Africa; Soil animals